Enzymatic production of xylooligosaccharides from Brazilian Syrah grape pomace flour: a green alternative to conventional methods for adding value to agricultural by-products - Costa, Joana R. (2018)
BACKGROUND: The aim of this work was to determine the most favorable conditions for the production of xylooligosaccharides (XOS) from Brazilian Syrah grape pomace. Chemical processes were performed using a rotatable central composite design, where the concentration of sulfuric acid or concentration of sodium hydroxide and grape pomace flour: solvent mass ratio were the dependent variables. Enzymatic production was also evaluated using xylanase produced by Aspergillus niger 3T5B8 and Viscozyme® enzymatic commercial cocktail. RESULTS: Chemical extraction allowed to recover 21.8 to 74.6% and 5.2 to 96.3% of total XOS for acid and alkaline processes, respectively. Enzymatic production using xylanase extracted up to 88.68 ± 0.12% of total XOS and up to 84.09 ± 2.40% with Viscozyme®. CONCLUSION: The present study demonstrated different feasible methods to produce high added value molecules, the xylooligosaccharides, from Syrah grape pomace flour, valorizing this major by‐product. The use of enzymatic cocktails demonstrated to be an alternative to the conventional methods, allowing to obtain an eco‐friendly and sustainable grape pomace extract.